2009
DOI: 10.1002/cphc.200900271
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of Finite‐Nucleus‐Size Effects in Relativistic Density Functional Computations of Indirect NMR Nuclear Spin–Spin Coupling Constants

Abstract: A spherical Gaussian nuclear charge distribution model has been implemented for spin-free (scalar) and two-component (spin-orbit) relativistic density functional calculations of indirect NMR nuclear spin-spin coupling (J-coupling) constants. The finite nuclear volume effects on the hyperfine integrals are quite pronounced and as a consequence they noticeably alter coupling constants involving heavy NMR nuclei such as W, Pt, Hg, Tl, and Pb. Typically, the isotropic J-couplings are reduced in magnitude by about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
90
2
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 82 publications
(98 citation statements)
references
References 54 publications
3
90
2
1
Order By: Relevance
“…The difference between the relativistic calculation result and experiment was later shown to be due to solvent effects. 166 Finite nucleus effects on J-coupling constants between Hg and a light atom were shown to be comparable to those of the HFCCs, 155 also reducing the magnitude of the coupling, and of comparable magnitude for Pb (below 10% for Pt). For the Hg-Hg coupling in a crown-ether complex of [Hg-Hg] 2 + , the finite nucleus effects reached 19%, and went up to 28% for the coupling in the free [Hg-Hg] 2 + ion.…”
Section: F Hyperfine Coupling J-couplingmentioning
confidence: 82%
See 2 more Smart Citations
“…The difference between the relativistic calculation result and experiment was later shown to be due to solvent effects. 166 Finite nucleus effects on J-coupling constants between Hg and a light atom were shown to be comparable to those of the HFCCs, 155 also reducing the magnitude of the coupling, and of comparable magnitude for Pb (below 10% for Pt). For the Hg-Hg coupling in a crown-ether complex of [Hg-Hg] 2 + , the finite nucleus effects reached 19%, and went up to 28% for the coupling in the free [Hg-Hg] 2 + ion.…”
Section: F Hyperfine Coupling J-couplingmentioning
confidence: 82%
“…The matrix elements of the ZORA FC operator remain finite for moderately large Z and the operator matrix elements can be converged in a meaningful way with respect to the basis set size. 154,155 Instead of sampling a finite electron density at a point nucleus, the quasi-relativistic form of the FC operator samples the density and its slope very close to the nucleus. If one were to use a hyperfine operator that is inconsistent with the approximate or an exact two-component method, such as the nonrelativistic form of the FC term, the results would not be meaningful and become singular in a complete basis.…”
Section: F Hyperfine Coupling J-couplingmentioning
confidence: 99%
See 1 more Smart Citation
“…The 1 J(Pb-H) value obtained for this system with the BP non-hybrid density functional was 2345 Hz with the four-component method, compared to an experimental estimate of around 2600-2800 Hz from extrapolations of measured couplings for methyl-substituted plumbanes. For comparison, a point-nucleus result from [201] obtained with ZORA and the PBE non-hybrid functional and converted to Hz ( 1 H, 207 Pb) would be 2836 Hz. In [201], it was shown that the use of a hybrid functional strongly increases the Pb-H J-coupling in plumbanes, while finite-nucleus corrections lead to a reduction again.…”
Section: Dks X2c-ksmentioning
confidence: 99%
“…The effects were found to be of comparable magnitude for Pb, but below 10% for Pt. For the Hg-Hg coupling in a crown ether complex of [Hg-Hg] 2+ , the finite-nucleus effects reached 19%, and went up to 28% for the coupling in the free [HgHg] 2+ ion [201]. The finite-nucleus effect on 'nuclear properties' has two aspects.…”
Section: Dks X2c-ksmentioning
confidence: 99%